Islam in Indonesia: Modernism, Radicalism, and the Middle East Dimension by Giora Eliraz (Brighton and Portland: Sussex Academic Press, 2004. 142 pages.) (American Journal of Islam and Society, 2005)
Southeast Asian Islam is receiving an increased amount of attention amongboth scholars and students. The direction has been toward understandingMuslim diversity and change, despite the still-existing perceptions among the public of a monolithic and static Islam. Fundamentalism still gains moreattention, partly due to its current influence and confusion. In this book,Giora Eliraz comparatively examines how the Middle Eastern Islamic modernistmovements influenced Islamic movements in the Malay-Indonesianworld throughout the twentieth century and contributed to the rise of contemporaryIslamic radicalism in Indonesia.Eliraz studies the transmission of modernist and/or radical ideas fromthe Middle East to Indonesia, the multiple organizations and strategieswithin Islamic movements, as well as the impacts of local and national valueson the distinct faces of Indonesian Islam. Despite the current emergenceof Islamic radicalism, the majority of the people continue to reject politicizedIslam. According to the author, the tradition of intellectual and organizationalpluralism has become the predominant characteristic ofIndonesian Islam.The book is divided into three chapters. Chapter 1 examines how thereformist ideas of Muhammad Abduh (1849-1905), his colleague Jamaluddinal-Afghani (1839-97), and Muhammad Rashid Rida (1865-1935) were transmittedto Southeast Asia (including Indonesia and the Malay Peninsula)through publications and networks, and how they were interpreted andapplied within the new environment. Thus, Islamic reformist ideas, particularlyfrom Egypt, influenced the rise of as well as the conflicts between themodernists, represented by the Muhammadiyah (established in 1912), andthe traditionalists, represented by the Nahdatul Ulama (NU, established in1926). In these two movements, Middle Eastern reformism underwent aprocess of localization that involved local preachers, activists, and scholars ...